Analisis Pengungkapan Modal Intelektual - Marfungatun Rahma; Minadi Wijaya; Tunggul Priyatama (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This study aims to analyze the effect of firm size, profitability, and leverage on intellectual capital disclosure in property and real estate companies listed on the IDX for the 2017-2019 period. The population in this study are property and real estate companies listed on the Indonesia Stock Exchange in 2017 - 2019. The sample used is 37 property and real estate companies with observations for three years totaling 111 units of analysis. The analytical method used is the multiple regression method. The results of this study indicate that firm size has a significant positive effect on intellectual capital disclosure, while profitability and leverage have no significant effect on intellectual capital disclosure.